Some features of the dynamics of suprathermal electrons after RF heating off at the Uragan-3M stellarator plasmas - Zamanov, N.V.; Pavlichenko, R.O.; Kulaga, A.E. (Вопросы атомной науки и техники, 2019)
For the past decades the microwave radiometry is a routinely used as diagnostic tool to obtain the information on temporal evolution and radial profile of the electrons temperature at Uragan-3M torsatron plasma experiments. However, in the case of low plasma density operation we observe the high level of emission at the frequencies that match the second and third harmonics of the extraordinary mode of electron cyclotron emission (ECE), after RF heating pulse off. This effect could be explained with the production of the suprathermal electrons. The present work describes the suprathermal electrons (SE) dynamics after turning off the RF heat pulse at the Uragan-3M torsatron (ne=2·10¹² cm⁻³ Te=300 eV, PRF=115 kW, B0=0.69 T). In the absence of the well-known suppressive echniques (resonant magnetic perturbations and massive gas injection) an attempt was made to describe the factors, which contribute to the generation of the suprathermal electrons for the Uragan-3M plasmas. The temporal evolution of the ECE emission intensity and it dependence on the working gas pressure in the torsatron vacuum chamber is presented. The level of the ECE emission shows strong correlation with other diagnostics (plasma density, plasma current, HXR and Hα emission intensity). The gradual increase of the pressure (after RF off) could be is one of the reasons that temporarily sustain the process of electron acceleration. The dependence of the time ECE emission on the rate in magnetic field change (δB) is also given. Протягом останніх десятиліть мікрохвильова радіометрія регулярно використовується для отримання інформації про часову еволюцію та радіальний профіль температури електронів під час плазмових експериментів на торсатроні Ураган-3М. Тим не менш, у випадку низькощільної плазми за допомогою цієї діагностики спостерігається поява випромінювання на частотах, відповідних другій і третій гармонікам незвичайної хвилі циклотронного випромінювання (ЕЦВ), після відключення імпульсу високочастотного нагріву. Цей ефект можна пояснити існуванням надтеплових електронів. Описані динаміка надтеплових електронів (НЕ) після виключення ВЧ-імпульсу на торсатроні Ураган-3М (ne=2·10¹² см⁻³, Te=300 еВ, PRF=115 кВт, B0=0,69 Tл). За відсутності відомих методів придушення (резонансні магнітні збурення і масивна інжекція газу) була зроблена спроба описати фактори, що сприяють генерації надтеплових електронів у плазмі Ураган-3М. Представлена тимчасова динаміка інтенсивності емісії ЕЦВ і її залежність від тиску робочого газу у вакуумній камері торсатрона. Рівень емісії ЕЦВ демонструє чітку кореляцію з результатами інших методів діагностики (щільність плазми, струм плазми, HXR і Hα). Поступове підвищення тиску (після відключення ВЧ-потужності) може бути однією з причин, які підтримують процес прискорення електронів. Також наведена часова залежність випромінювання ЕЦВ від швидкості зміни магнітного поля (δB/δt). В последние десятилетия микроволновая радиометрия регулярно используется в качестве диагностического инструмента для получения информации о временной эволюции и радиальном профиле температуры электронов в экспериментах на торсатроне Ураган-3М. Тем не менее, в случае низкоплотной плазмы при помощи этой диагностики наблюдается появление излучения на частотах, соответствующих второй и третьей гармоникам необыкновенной волны циклотронного излучения (ЭЦИ), после отключения импульса высокочастотного нагрева. Этот эффект можно объяснить существованием надтепловых электронов. Описана динамика надтепловых электронов (НЭ) после выключения ВЧ-импульса на торсатроне Ураган-3М (ne=2·10¹² см⁻³, Te=300 эВ, PRF=115 кВт, B0=0,69 Tл). В отсутствие известных методов подавления (резонансные магнитные возмущения и массивная инжекция газа) была предпринята попытка описать факторы, способствующие генерации надтепловых электронов в плазме Ураган-3М. Представлена временная динамика интенсивности эмиссии ЭЦИ и ее зависимость от давления рабочего газа в вакуумной камере торсатрона. Уровень эмиссии ЭЦИ демонстрирует строгую корреляцию с результатами других методов диагностики (плотность плазмы, ток плазмы, интенсивность HXR и Hα). Постепенное повышение давления (после отключения ВЧ-мощности) может быть одной из причин, которые поддерживают процесс ускорения электронов. Также приведена временная зависимость излучения ЭЦИ от скорости изменения магнитного поля (δB/δt).